Estudo de proteção contra descargas atmosféricas diretas em uma unidade de minigeração fotovoltaica distribuída - Lisboa, Bruno Rodrigues (2018)
The use of Distributed Generation (DG) is propelled by a strong tendency by consumer units to reduce their energy costs. This dissertation aims to present gains in the area of protection against lightning, applied to photovoltaic generation systems. For that, a case study was carried out in a distributed photovoltaic minigeration unit located in the northeastern semi-arid region, in the city of Mossoró, in the state of Rio Grande do Norte. In this work the incidence of atmospheric discharges is analyzed through the traditionally used and predicted methods in gls NBR 5419: 2015, as the protection angle model and the rolling ball technique. We also performed an incidence analysis using the gls EFD method, which was recently proposed, and presents gains over traditional methods, since it considers in the simulation besides the geometry of the structure, physical parameters such as field distribution electrical, relative permissiveness of existing materials and dielectric medium. The three incidence models showed the need to carry out the protection installation in the structure. In this way four protection scenarios were analyzed, being the first with captor around the plates, containing frames in aluminum (A1); already the second scenario, the captor is above the photovoltaic modules (A2), which also has aluminum in the frames; the scenario (B1), where the uptake occurs around the structure to be protected, however the photovoltaic panel frame is made of fiberglass; and the scenario (B2) in which uptake is structured above the photovoltaic panels and the frame of the modules is constituted by glass fiber. In scenarios A1 and A2, protection against direct atmospheric discharges was not satisfactory in the incidence analysis of the gls EFD method, since there was incidence of direct discharges on the plates. In the B1 and B2 scenarios the protection was satisfactory, not having a direct incidence of atmospheric discharges, due to the elimination of the natural captor with the replacement of the aluminum frame by fiberglass.